2004
DOI: 10.1128/jvi.78.10.5139-5146.2004
|View full text |Cite
|
Sign up to set email alerts
|

Unspliced Rous Sarcoma Virus Genomic RNAs Are Translated and Subjected to Nonsense-Mediated mRNA Decay before Packaging

Abstract: Retroviruses package full-length, unspliced RNAs into progeny virions as dimerized RNA genomes. They also use unspliced RNAs as mRNAs to produce the gag and pol gene products. We asked whether a single Rous sarcoma virus (RSV) RNA can be translated and subsequently packaged or whether genomic packaging requires a nontranslated population of RNAs. We addressed this issue by utilizing the translation-dependent nonsense-mediated mRNA decay (NMD) pathway. NMD is the selective destruction of mRNAs bearing premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 50 publications
1
63
0
Order By: Relevance
“…Previous results have shown that termination codons placed throughout the gag coding region destabilize the unspliced RSV transcript (Barker and Beemon 1991) by the NMD pathway (LeBlanc and Beemon 2004). Knowing that the pol gene is translated much less frequently than gag (Swanstrom and Wills 1997), we asked whether termination codons in pol would cause degradation of the unspliced RNA.…”
Section: Translation Of Ptcs In Pol Destabilize the Unspliced Rnamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous results have shown that termination codons placed throughout the gag coding region destabilize the unspliced RSV transcript (Barker and Beemon 1991) by the NMD pathway (LeBlanc and Beemon 2004). Knowing that the pol gene is translated much less frequently than gag (Swanstrom and Wills 1997), we asked whether termination codons in pol would cause degradation of the unspliced RNA.…”
Section: Translation Of Ptcs In Pol Destabilize the Unspliced Rnamentioning
confidence: 99%
“…This decay diminishes gradually when the PTC is in the final 150 nt of the gag gene, approaching the natural termination codon (Barker and Beemon 1994). Additionally, LeBlanc and Beemon (2004) showed that this decay depends on translation and the critical NMD factor Upf1, implicating the NMD machinery. Since this regulation occurs on an unspliced RNA, it contrasts with previous reports in higher eukaryotes that splicing is necessary to distinguish a PTC from a normal termination codon (Maquat 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the presence of EJCs downstream from TCs was thought to be an essential signal to identify the TC as premature and elicit NMD (Maquat 2004), but it is meanwhile clear that mammalian NMD can also occur in the absence of an EJC downstream from the PTC (Zhang et al 1998;Rajavel and Neufeld 2001;Delpy et al 2004;LeBlanc and Beemon 2004;Buhler et al 2006;Matsuda et al 2007;Eberle et al 2008;Singh et al 2008). Since NMD is triggered upon aberrant translation termination, which can only occur after at least one ribosome has passed the entire coding sequence and thereby removed the EJCs, NMD-targeted mRNAs without introns downstream from the TC are most likely devoid of any bound EJCs, and we therefore refer to this NMD pathway as "EJC-independent NMD."…”
Section: Introductionmentioning
confidence: 99%
“…Instead, unspliced HIV-1 RNA functions interchangeably as an mRNA template for translation and as genomic RNA that is packaged [16]. A similar conclusion was reached for Rous sarcoma virus (RSV) in a study that evaluated the relationship between translation-dependent nonsense mediated decay and RNA packaging [48].…”
Section: Introduction Retrovirus Primary Transcription Product Can Fumentioning
confidence: 68%